2018
DOI: 10.4001/003.026.0202
|View full text |Cite
|
Sign up to set email alerts
|

Non-Host Status of Commercial Export Grade Lemon Fruit (Citrus limon(L.) Burman f. cv. Eureka) forCeratitis capitata,Ceratitis rosa,Ceratitis quiliciiandBactrocera dorsalis(Diptera: Tephritidae) in South Africa

Abstract: Markets importing citrus fruit including lemons, Citrus limon (L.) Burman f., from South Africa require that the fruit be free of fruit fly pests (Diptera: Tephritidae). Historically there has been no fruit fly infestation recorded on lemons destined for export from South Africa. In this study, we assessed the host status of commercial export grade Eureka lemons, Citrus limon (L.) Burman f. cv. Eureka, for four fruit fly pest species of economic importance in South Africa: Ceratitis capitata (Wiedemann), Cerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In surveys in commercial Eureka lemon orchards in South Africa, no eggs nor larvae of fruit flies (including B. dorsalis ) were recorded on fruit that had just been harvested. This was despite the presence of fruit flies, including B. dorsalis , in the surveyed lemon orchards (Manrakhan et al 2018). Theron et al (2017) recorded no infestation of B. dorsalis on citrus fruit sampled on the ground (detached fruit) in South Africa despite the presence of the pest in the areas that they sampled.…”
Section: Discussionmentioning
confidence: 95%
“…In surveys in commercial Eureka lemon orchards in South Africa, no eggs nor larvae of fruit flies (including B. dorsalis ) were recorded on fruit that had just been harvested. This was despite the presence of fruit flies, including B. dorsalis , in the surveyed lemon orchards (Manrakhan et al 2018). Theron et al (2017) recorded no infestation of B. dorsalis on citrus fruit sampled on the ground (detached fruit) in South Africa despite the presence of the pest in the areas that they sampled.…”
Section: Discussionmentioning
confidence: 95%
“…Three species of fruit flies affect citrus in the region: the Mediterranean fruit fly, Ceratitis capitata (Wiedemann), the Natal fruit fly, Ceratitis rosa Karsch and the oriental fruit fly, Bactrocera dorsalis (Hendel) [4]. In South Africa, commercial export grade lemon, Citrus limon (L.) Burman f., was shown to be a non-host for T. leucotreta and the three fruit fly pests of citrus [5,6]. Lime, Citrus aurantifolia (Christm.)…”
Section: Introductionmentioning
confidence: 99%
“…Swingle, C. hystrix DC., Litchi chinensis Sonn., and Passiflora edulis Sims is unclear. Previous studies in the laboratory showed that lemons (Citrus limon (L.) Osbeck) and lychee are relatively poor hosts for B. dorsalis (Armstrong and Follett, 2007;Manrakhan et al, 2018). Ripe and unripe fruits of Passiflora edulis were reported as natural hosts in Comoros and Hawaii (Akamine et al, 1974;Hassani, 2017).…”
Section: Introductionmentioning
confidence: 99%